USE OF SUBSTRATES IN THE PROPAGATION OF DRAGON FRUIT VARIETIES VIA CUTTINGS - da Silva, Edgley Soares; de Oliveira, César Augusto Batista; Cruz, Ana Bárbara de Souza; Monteiro Neto, João Luiz Lopes; Gonçalves, Anderson Carlos de Melo; Reyes, Veronica Nathaly Arevalo (Seven Editora, 2026)
The production of pitaya seedlings can be carried out via cutting, grafting or micropropagation. Propagation via cuttings is one of the most used, due to its advantages related to the shorter time to obtain the seedlings and to preserve the characteristics of the mother plants. In the production of seedlings by cuttings, one of the main criteria to be considered is the use of substrates, as it depends on obtaining vigorous and productive plants. In this sense, it aimed to evaluate the use of different substrates in propagation via cuttings of different varieties of pitaya. The experimental design was completely randomized in a 3 x 4 factorial scheme, with three replications. Three varieties of pitaya were tested: red, white and yellow and four substrates: S1 - carbonized rice husk, S2 - aged wood sawdust, S3 - earthworm humus and S4 - poultry litter. After 45 days of planting, the number of roots, length of the longest root, length of the shortest root, number of shoots, fresh root mass and dry root mass were evaluated. It was concluded that the aged wood sawdust and carbonized rice husk substrates are promising for the production of pitaya seedlings per cutting. The varieties of pitaya Vermelha and Amarela have better development when grown under aged wood sawdust. The white pitaya variety grows best under carbonized rice husks.